Introducing seasonal influenza vaccine in low-income countries: an adverse events following immunization survey in the Lao People's Democratic Republic - Phengxay, Manilay (Influenza Other Respir Viruses, 2015)
OBJECTIVE: In 2012, Lao PDR introduced seasonal influenza vaccine in pregnant women, persons aged ≥50 years, persons with chronic diseases, and healthcare personnel. We assessed adverse events following immunization (AEFI). METHODS: We used a multistage randomized cluster sample design to interview vaccine recipients. FINDINGS: Between April and May 2012, 355 902 were vaccinated. Of 2089 persons interviewed, 261 (12·5%) reported one or more AEFI. The most commonly reported AEFIs were local reactions. No hospitalizations or deaths were reported; 16% sought medical care. Acceptance and awareness of vaccination were high. CONCLUSIONS: Following the introduction of seasonal influenza vaccine in Lao PDR, self-reported adverse events were mild.